STUDI GERAKAN IDEOLOGI PARTAI POLITIK PADA PEMILU 2019 - Iswandi Iswadi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2020)
The ideology contestation is basically a classic polemic, where after independence the ideology of Islam was confronted with nationalism and took root until now (reform). However, the momentum of the 2019 election political contestation was again marked by the struggle of ideology namely ideology of Islamism and nationalism. The polemic began with the emergence of religious issues that were raised on the surface of political actors as a hegemony in taking the sympathy of voters. The existence of religion as a central issue began in 2016-2017 related to the prosecution of Ahok who insulted religious values ​​(Islam), and among the political parties involved in the demonstrations namely PPP, PKS, PBB, and PKB. In that momentum the beginning of the revival of Islamic ideology as the power in defending Islamic sovereignty. Judging from the ideology of political parties in Indonesia in the 2019 election political contestation, the ideology of political parties based on the statutes and bylaws (AD / ART) that the ideology applied can be classified into three parts namely ideology Nationalism, Islamism, and Nationalist-Religious, and the three ideologies. This can be proven based on the results of a survey from Australia 2017-2018 based on the voters. However, political parties based on multiple ideologies, PAN, PKB and Democrats, each have priority orientation. PAN and PKB tend to polarize the values ​​of Islamism (religious), while Democrats are more dominated by nationalist issues. The concept of Islamic political ideology, in the context of political contestation in political party elections, is basically a necessity to implement the values ​​of ri'ayah, taqwin, irshad and ta'dib through political education, or campaign in elections to achieve mutual benefit, both parties whose ideology Islamism, nationalism and nationalist-religious, so as to build the moralistic side of society, and intelligence in responding to the issues that exist in the election apart from that, political parties in confronting political contestation the emphasis of the movement must reflect the value of poverty, the three ideologies have been packaged in the values ​​of Pancasila in the third principles of Indonesian unity. Asbtak Kontestasi ideology pada dasarnya polemik klasik, dimana pasca kemerdekaan ideologi islam dihadapkan dengan nasionalisme dan mengakar sampai sampai saat ini (reformasi). Akan tetapi momentum pemilu 2019 kontestasi politik kembali diwarnai pergulatan ideology yakni ideology islamisme dan nasionalisme. Polemik tersebut berawal dengan mencuatnya isu keagamaan yang dimunculkan dipermukaan pelaku politik sebagai hegemoni dalam mengambil simpati pemilih. Eksistensi agama sebagai sentral isu berawal tahun 2016-2017 terkait penuntutan terhadap ahok yang melecehkan nilai-nilai agama (islam), dan diantara partai politik yang terlibat dalam demonstrasi yakni PPP, PKS, PBB, dan PKB. Dalam momentum tersebut awal mencuatnya kembali ideologi islam sebagai of the power dalam mempertahan kedaulatan Islam. Menilik ideologis partai politik di Indonesia pada konstestasi politik pemilu 2019, ideology partai politik berdasarkan anggaran dasar dan anggaran rumah tangga (AD/ART) bahwa ideologi yang diterapkan dapat diklasifikasikan menjadi tiga bagian yakni ideology Nasionalisme, Islamisme, dan Nasionalis-Religius, dan ketiga ideology tersebut dapat dibuktikan dengan berdasarkan hasil survey dari asutralia 2017-2018 berdasarkan pemilih. Namun demikian partai poltik yang berasaskan ideologi ganda, PAN, PKB dan Demokrat, masing-masing memiliki kiblat prioritas. PAN dan PKB condong polarisasi nilai-nilai islamisme (religious), sedangkan Demokrat lebih didominasi oleh isu-isu nasionalis. Konsep ideology politik islam, dalam konsteks kontestasi politik dalam pemilu partai politik pada dasarnya sebuah keharusan mengimplementasikan nilai-nilai ri’ayah, taqwin, irsyad dan ta’dib melalui pendidikan politik, ataupun kampanye dalam pemilu guna mencapai kemaslahatan bersama, baik partai yang berideologi islamisme, nasionalisme dan nasionalis-religius, sehingga terbangun sisi moralistik masyarakat, dan kecerdasan dalam menanggapi isu-isu yang ada dalam pemilu. selain dari itu partai politik dalam menghadapi konstestasi politik penekanan gerakannya harus mencermikan nilai kemaslahan, ketiga ideology tersebut telah kemas dalam nilai-nilai pancasila pada sila ketiga persatuan Indonesia.